The Newcomes : memoirs of a most respectable family - Thackeray, William Makepeace, 1811-1863 (Floating Press, 2010)
The Newcomes is a sprawling novel by English author William Makepeace Thackeray, who also penned the popular novel Vanity Fair. Considered by many critics to be Thackeray's finest work, The Newcomes follows the fortunes of several generations of the Newcome family, a nouveau riche clan that begins to mingle and intermarry with the British aristocracy. In particular, the novel focuses on the relationship between Colonel Newcome and his artistically inclined son, Clive.